Histories of Abolition, Critiques of Security - McQuade, Brendan (Social justice, 2018)
The contemporary debate about abolition and its relation to wider anti-capitalist and anti-racist struggles can be read as reproducing the tired opposition between reform and revolution, between gradual incrementalism and immediate disruptive action. This false dichotomy can be resolved by returning the holistic and historical analysis of abolition democracy offered by W.E.B. Du Bois’ in his classic work Black Reconstruction. Du Bois offers an alternative mandate for abolitionist praxis: one which highlights the interplay of disruptive direct action and incremental change within a historically informed understanding of a particular social struggle. Understood in these terms, abolition becomes a critically important and neglected component of the revolutionary tradition: Abolition is the foil of bourgeoisie security.